Making it up in the office : a study on women and their presentation of self at work. - Tan, Yee Wen. (2013)
This study aims to understand the makeup practices of the average female office employee in Singapore; how having to wear of make-up can work in or against their favour, and whether they conform to or attempt to subvert these appearance norms. A total of 8 in-depth interviews are conducted, with women of different ages and ethnicity backgrounds. The research has found that makeup often used in the workplace to achieve the appearance of competency, confidence and productivity. Consequently, this has effects on the performance of the respondents at work. In analyzing the experiences and choices made by the women in the sample, the author concludes that the women do not necessarily submit themselves blindly to the oppressive beauty regimes that they are obliged to undertake, but also exert some autonomy in the making of informed choices as well as redefining the use of makeup in the face of the institutional constraints.